Primary ovarian mucinous carcinoid tumor: A case report and review of literature - Wen-Wei Hsu; Tsui-Lien Mao; Chi-Hau Chen (Elsevier, 2019)
Objective: Only a few cases of primary ovarian mucinous carcinoid tumor have been documented in the literature till date. We present a case of primary ovarian mucinous carcinoid tumor, atypical type, and review the reported cases. Case report: A 33-year-old woman with a left ovarian tumor was diagnosed with primary ovarian mucinous carcinoid tumor, atypical type. She underwent left salpingo-oophorectomy and ipsilateral lymph node dissection. After 5 years, the tumor recurred on the right side, with large para-aortic lymphadenopathy that caused hydronephrosis. Complete surgical staging was performed, followed by nine cycles of weekly paclitaxel and gemcitabine. The tumor progressed after discontinuing the chemotherapy, and the patient died of disease 26 months after recurrence. Conclusion: Our patient demonstrated a more aggressive clinical course compared to that reported in previous literature. Based on this experience, complete surgical staging is highly recommended after the patient accomplished her fertility plan. Ovarian carcinoid tumors are relatively chemoresistant compared with epithelial ovarian cancers. The regimen of weekly paclitaxel and gemcitabine stabilized the disease but did not reach remission of the tumor. Further studies are required to determine the appropriate chemotherapy regimen. Keywords: Carcinoid, Mucinous, Ovary